One- and two-dimensional quantum lattice algorithms for Maxwell equations in inhomogeneous scalar dielectric media. II: Simulations. Issue 1 (1st February 2021) - Vahala, George; Soe, Min; Vahala, Linda; Ram, Abhay K.
Abstract : Long-time quantum lattice algorithm (QLA) simulations are performed for the multiple reflection–transmission of an initial electromagnetic pulse propagating normally to a boundary layer region joining two media of different refractive index. For these one-dimensional (1D) simulations, there is excellent agreement between x -, y - and z -representations, as well as very good agreement with nearly all the standard plane wave boundary condition results for reflection and transmission off a dielectric discontinuity. In the QLA simulation, no boundary conditions are imposed at the continuous, but sharply increasing, dielectric boundary layers. Two-dimensional (2D) QLA scattering simulations in the x – z plane are performed for an electromagnetic pulse interacting with a conical dielectric obstacle for the 8–16 qubit model.